Praktik Foto Prewedding di Indonesia: Definisi, Tujuan, dan Tinjauan Hukumnya dalam Perspektif Islam - Nasrudin, Ega; Nurti Budiyanti; Elan Sumarna (Nizham Jurnal Studi Keislaman, 2024)
This study aims to find out how the review of Islamic law on pre-wedding practices. The method used in this research is library research. Sources of data used in this study include books and journal articles. The results of the study show that pre-wedding photography is an activity of taking pictures carried out by couples who are not legally husband and wife or before marriage. Some of the goals of the community doing pre-wedding photos are to document the moments of happiness of the bride and groom, the desire of a pair of husband and wife to make memories, to beautify wedding invitations, to be attached to souvenirs distributed at weddings, to be used as decoration or display during the wedding process , to simply follow others, and to follow trends. There are differences of opinion in determining the law of the practice of pre-wedding photos. The first opinion states that pre-wedding photos are haraam because they can lead a prospective husband and wife closer to adultery.